Assessment of interstate freight vehicle characteristics and impact of future emission and fuel economy standards on their emissions in India. (September 2017) - Malik, Leeza; Tiwari, Geetam
Abstract: Road freight in India plays a vital role in the economic growth of our country. Rising energy consumption and the environmental impacts by freight vehicles is constantly monitored through the introduction of stringent emission standards and through the promotion of fuel efficiency policies. However, little information is available on freight activity data (vehicle-kilometre) and their fleet characteristics (vehicle age, annual mileage, fuel economy etc.) to assess these policies. Therefore, the paper analyses the existing fleet characteristics in terms of age, annual mileage, fuel economy, fuel type used etc. for the freight vehicles used for "interstate" or "intercity" mobility on National Highways. Origin-Destination surveys and traffic volume counts are conducted at ten locations along major National Highways to capture the fleet characteristics. Based on the results, emission outlook for the proposed emission standards and fuel economy standards for freight vehicles is presented. Significant emission reductions are expected if emission standards are nationwide and timely implemented. Further, the requirement of country representative survival rates is highlighted. Highlights: Assessment of inter-state freight vehicle activity data and their fleet characteristics in India. Emission outlooks for proposed emission and fuel economy standards for freight vehicles. Requirement of early transitioning to the stringent emission standards due to higher fleet turnover. Necessity of country representative survival estimates.